The wind in the willows - Grahame, Kenneth, 1859-1932.; Green, Peter, 1924- (New York : Oxford University Press, 1983)
The escapades of four animal friends who live along a river in the English countryside--Toad, Mole, Rat, and Badger.
Originally published : London : Methuen, [1908].
Bibliography: p. xxi-xxiii.
Keywords: Animals -- Fiction